Antiischemic properties of the Trka-receptor agonist, the nerve growth factor 4-th loop mimetic - E. S. Pekeldina; E. O. Ionova; I. A. Mirochkina; A. V. Sorokina; V. N. Stolyaruk; I. B. Tsorin; T. A. Gudacheva; S. A. Kryzhanovskii (Фармакокинетика и Фармакодинамика, 2018)
Resume. Relevance. One of the actual problems facing modern medical science is the study of mechanisms and the search for effective ways to activate tissue neovascularization. A possible approach to the decision of this problem is the use of TrkA receptor agonists to activate angiogenesis and, as a consequence, improve the vascularization of ischemic tissues. The aim of this investigation was to study the angiogenic and antiischemic activity of the TrkA receptor agonist the nerve growth factor 4th loop dipeptide mimetic the GK-2 compound. Methods. Experiments were performed on models of hind limb ischemia and myocardial infarction in rats. The compound GK-2 (1 mg/kg) was administered intraperitoneally for 14 days. Effects were evaluated using light microscopy and two-dimensional echocardiography. Results. In the model of the hindlimb ischemia in rats, it was shown that GK-2 (1 mg/kg, i.p.) significantly enhances the vascularization of the ischemic sural muscle. The vascularization index of ischemic tissue in animals treated with GK-2 was almost 2 times higher than in control - 27794 (25218 t 35941) and 14725 (9030 t 19630), respectively (p < 0.001). According to light microscopy, the studied compound reduces the intensity of tissue damage. Under conditions of experimental myocardial infarction, the GK-2 compound reduces the pathological remodeling intensity of the heart left ventricle. Conclusion. It can be assumed that the antiischemic effect of GK-2 is associated with increased vascularization of the affected tissue, i.e. with the stimulation of angiogenesis.